2017
DOI: 10.1186/s12890-017-0525-0
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula oxygen therapy versus conventional oxygen therapy in patients with acute respiratory failure: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundAcute respiratory failure (ARF) is a common and life-threatening medical emergency in patients admitted to the hospital. Currently, there is a lack of large-scale evidence on the use of high-flow nasal cannulas (HFNC) in patients with ARF. In this systematic review and meta-analysis, we evaluated whether there were differences between HFNC therapy and conventional oxygen therapy (COT) for treating patients with ARF.MethodsThe EMBASE, Medline, and Wanfang databases and the Cochrane Library were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
0
25
2
4
Order By: Relevance
“…HFNC is a novel oxygen therapy developed in recent years, in which oxygen at a certain concentration mixed with highflow gas is directly delivered to patients through a nonsealed nasal cannula [6,7]. is oxygen therapy has been assessed by many studies and can be applied to patients with acute hypoxemic respiratory failure, status-post surgery, and respiratory failure without tracheal intubation, immunosuppression, and cardiac insufficiency, thus effectively improving oxygenation [8][9][10][11][12][13][14][15]. However, few studies have confirmed the efficacy of HFNC in treating bronchial asthma, focusing mainly on pediatric and neonatal patients [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…HFNC is a novel oxygen therapy developed in recent years, in which oxygen at a certain concentration mixed with highflow gas is directly delivered to patients through a nonsealed nasal cannula [6,7]. is oxygen therapy has been assessed by many studies and can be applied to patients with acute hypoxemic respiratory failure, status-post surgery, and respiratory failure without tracheal intubation, immunosuppression, and cardiac insufficiency, thus effectively improving oxygenation [8][9][10][11][12][13][14][15]. However, few studies have confirmed the efficacy of HFNC in treating bronchial asthma, focusing mainly on pediatric and neonatal patients [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ HFNC was initially utilized as an alternative breathing support for premature infants to maintain positive airway pressure [37][38][39] ; however, there is a propensity to use HFNC therapy in adults with respiratory distress 8,40,41 . In the latest meta-analysis conducted by Zhu and colleague 40 , HFNC had significantly effect on reducing post-extubation respiratory failure rate, respiratory rates, and increasing PaO 2 , comparing with conventional oxygen therapy in patients after planned extubation.…”
Section: Discussionmentioning
confidence: 99%
“…The same groups advise against HHFNC for those patients in whom alveolar collapse is the main mechanism of dyspnoea, as the PEEP delivered by HHFNC is inferior to that delivered by full facemasks. This makes HHFNC of less use in obesity, acute pulmonary oedema or following abdominal surgery . It is also considered contraindicated in epistaxis, base of skull fracture, upper airway surgery or nasal obstruction because of the risk of mucosal ulceration from the nasal prongs, decreased access for certain surgical procedures and an unobstructed path to the HHFNC airflow …”
Section: What Are the Contraindications For Hhfnc?mentioning
confidence: 99%
“…HHFNC has been recommended for spontaneously breathing adults with hypoxemia, or discomfort from increased respiratory effort. 5,[8][9][10][11] It has been used in adults with acute respiratory failure, 12 pneumonia, 12 immunocompromise, 13 during airway procedures, 14 post-extubation 15 and palliative care. 3,16 The utility of HHFNC in hypercapnic respiratory failure is still uncertain.…”
Section: What Are the Indications For Hhfnc?mentioning
confidence: 99%
See 1 more Smart Citation